The Effectiveness of The Application Wordwall Learning Media In Improving The Ability of Writing Official Letters In Indonesian Learning For Students VII Class SMP Negeri 13 Kota Bengkulu - Sely Ariska; Salamah; Dina Putri Juni Astuti (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the effectiveness of the application wordwall media in improving the ability to write official letters in Indonesian language learning for seventh-grade students of SMP Negeri 13 Kota Bengkulu. This research uses quantitative research with a quasi-experiment method. The population in this study were all seventh-grade students, while the samples were from VII A and VII B classes consisting of control and experimental classes. Techniques for collecting data are observation, instrument tests, and documentation. The results of the study The ability to write official letters of VII grade students at SMP Negeri 13 Bengkulu City from the results of the study is the average percentage of the experimental class 79.48%. Meanwhile, the average percentage of the control class is 69.64%. Judging from the posttest value for each indicator varies where there are four indicators. For the effectiveness of the application of Wordwall learning media in improving the ability to write official letters from the data value sign. 0.05 (0.000<0.05), then Ha is accepted and Ho is rejected.